Assessing the Legal Strength of the Exceptio Non Adimpleti Contractus (ENAC) in Residential Sale and Purchase Disputes in Indonesia - Wijaya, Niko; Djaja, Benny (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Disputes over home sales and purchases constitute one of the most common forms of contractual conflict, particularly when one party fails to fulfill its obligations under the agreement. In this context, the exceptio non adimpleti contractus (ENAC) serves as a crucial mechanism for maintaining a balance of rights and obligations. This study aims to analyze the legal foundations, concepts, and principles of ENAC as reflected in the Civil Code, scholarly doctrine, and jurisprudence, and to examine its application in home sale and purchase disputes through judicial interpretation and evidentiary patterns related to default. Employing normative legal research methods with statutory, doctrinal, and case-based approaches, the study finds that ENAC is consistently applied by judges through the principles of proportionality, good faith, and the evidentiary strength of documentary proof. These findings confirm that ENAC plays a significant role in ensuring legal protection and preventing contractual inequities. The study concludes that the application of ENAC reinforces legal certainty and promotes compliance with contractual obligations in property transactions in Indonesia.